Interval Prediction of Landslide Displacement Using a Pretrained Large Time Series Model Based on Large-scale Cross-domain Data - Xuhuang Du; Cheng Lian; Bo Xu; Zhiyong Qi; Jin Yuan; You Mou; Bing Li (Journal of Applied Science and Engineering, 2025)
Assessing the uncertainty in landslide displacement prediction is essential for improving the dependability of landslide early warning systems. In this study, we employ advanced Transformer-based models to develop robust probabilistic forecasting methods, which are used to construct reliable prediction intervals for landslide displacement. Furthermore, to overcome the challenge of limited data availability, a common issue due to the high costs associated with monitoring landslide displacement, we leverage Lag-LLama, a large pretrained model initially trained on extensive cross-domain time series data, to enhance the probabilistic prediction of landslide displacement. Our experiments, conducted on six real-world landslide displacement datasets from China, demonstrate that the Lag-LLama-based approach significantly outperforms state-of-the-art time series forecasting models in the context of landslide displacement interval prediction. These results highlight the potential of large pre-trained models in addressing data scarcity and improving predictive accuracy in geohazard monitoring applications.